The Influence of Moral Self-Knowledge on the Manifestation of Egocentrism in Adolescence (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is devoted to the issues of the influence of moral self-awareness on the manifestation of egocentrism in adolescence. First of all, an analysis of theoretical data on the issues of morality and moral self-awareness is presented. Also, based on empirical data, the issue of the influence of moral self-awareness on the manifestation of egocentrism in adolescence was investigated.